Periodization of late medieval necropolis in the Lower Serbian Danube Basin - Radičević Dejan (Starinar, 2008)
Most of the necropolis investigated in the Lower Danube basin have been generally dated between the 12th and 14th centuries. However, the grave finds indicate that there are significant differences between certain necropolis and against that background it is apparent that they could not date from the same time period. The main characteristic of the necropolis in Korbovo Vajuga and Prahovo are numerous bracelets and various variants of the earrings with biconical pendants. There were also found the earrings with granulated nodules, hoops with coils of wire on their lower segment and earring with spherical pendant decorated with the pseudo granulation. The necropolis at the sites Svetinja in Stari Kostolac and the cemeteries at Mala Vrbica, Kličevac and Čoka Arte are also chronologically close to the above mentioned necropolis. Another group includes the necropolis at which the mentioned finds are entirely lacking. These are the necropolis Kod Groblja in Stari Kostolaca as well as the cemeteries at Čezava, Manastir, Boljetin Ravna, Hajdučka Vodenica, Ušće Porečke reke, Ljubičevac and Mihajlovac. Between these two groups of clearly distinguished necropolis are the cemeteries at Ribnica and Brza Palanka characterized by the mixed finds known from both groups of the necropolis. The beginning of interment in the cemeteries at Korbovo, Prahovo and Svetinja could be dated not before the second half of the 12th century, while at Vajuga it is more precisely dated in the end of that century. The question is how long these cemeteries could have been in use. The coin finds confirm without doubt that they had been in use during the first decades of the 13th century and the cessation of burying could be related to the Mongolian invasion, which affected these regions in the beginning of the fifth decade of the 13th century at the latest. The gradual disappearance of the earlier jewelry could be observed through the rare finds in the 13th century cemeteries, while they are entirely lacking in the later burials. The changes in the inventory of the necropolis relate also to the appearance of new decorative objects including the jewelry made of small ornamental plates or the earrings shaped as question mark. Generally speaking, these cemeteries are characterized by smaller quantity of grave goods and among them are much more frequent the elements of clothing (buckles, buttons, clasps), which are almost entirely lacking in the earlier cemeteries. It could not be precisely established how long these cemeteries had been in use only on the basis of the grave finds but the cessation of burying could be indirectly related to the Turkish conquest of this part of the Danube valley.